Comparing the Safety and Efficacy of Outpatient Parenteral Antibiotic Therapy Versus Hospital-Based Antibiotic Therapy in Patients with Infective Endocarditis: A Systematic Review and Meta-Analysis - Mohanad A. Alkuwaiti; Faisal A. Al-Harbi; Feras A. Alkuwaiti; Ahmed K. Alsaif; Hamza Ashraf (American Journal of Therapeutics, 2026)
Introduction: Infective endocarditis (IE) requires 4 to 6 weeks of intravenous antibiotics. Outpatient parenteral antibiotic therapy (OPAT) is increasingly used and guideline endorsed, but IE-specific comparative evidence is limited, as prior meta-analyses pooled single-arm data without an inpatient comparator. We compared the safety and efficacy of OPAT versus continued hospital-based antibiotic therapy. Methods: This systematic review and meta-analysis followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020. PubMed/MEDLINE, Embase, Cochrane CENTRAL, and Web of Science were searched to 18 April 2026 for comparative studies of adults with IE. Two reviewers screened using Rayyan and extracted data, and risk of bias was assessed with Risk Of Bias In Non-randomized Studies of Interventions. Random-effects meta-analyses (DerSimonian–Laird) produced risk ratios with 95% confidence intervals (CIs) (RevMan 5.4). Results: Five comparative studies (3497 adults) were included. OPAT was associated with lower all-cause mortality (risk ratio [RR]: 0.40, 95% CI: 0.18–0.90; I 2 = 87%, P = 0.03) and with lower acute kidney failure (RR: 0.71, 95% CI: 0.59–0.86, P = 0.0004). No significant differences were seen for readmission (RR: 1.09), relapse (0.73), valve replacement (1.15), arrhythmia, sepsis, stroke, embolic complications, or heart failure. Conclusions: In appropriately selected, stabilized patients, OPAT was associated with lower all-cause mortality and acute kidney failure, with no significant differences in major other adverse events. Protocol: CRD420261410723.